Going legal. Issue 1 (4th December 2012) - Lopez, Tony; Howells, Rachel; Lindsay, Simon
Abstract : A 16-year-old girl is admitted with a paracetamol overdose, but refuses treatment. This article explores the legal, ethical and practical aspects of this case, which led ultimately to an application to the court for a judicial order.